A lamp brighter than foxfire: poems - Nicholson, Andrew S., author; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2015)
Opening the space between the ordinary and the visionary, the poems in A Lamp Brighter than Foxfire uncover an intimate relationship with the world around them, from Las Vegas to Italy to the American Midwest. From a lime glowing in an orchard to a miraculous childhood attempt at levitation, Andrew S. Nicholson's poems ground themselves in the commonplace and leap for the luminous. Central to this collection are poems that retell stories of Jacob from the Old Testament, relocated behind casinos, glimpsed in miniature on kitchen floors, and heard speaking in a moment of decay. Through these retellings, Nicholson examines the creation of self, family relationships, and a generative sense of the divine--provided by publisher.
Keywords: American poetry